Organizational Culture, Communication, and Job Satisfaction on Employee Performance in the Regional Disaster Management Agency - Arsenius Purwanto; Alim Bachri; Zainal Arifin (International Journal of Multi Discipline Science, 2022)
This study aims to analyze the influence of organizational culture, communication, and job satisfaction on employee performance. This type of research was explanatory research, to test the relationship between several variables through testing several hypotheses. The sample population in this study were 54 employees who work in regional disaster management agencies in North Barito Regency, Central Kalimantan Province by distributing questionnaires and then processing using multiple regression analysis. The results showed that organizational culture, communication, and job satisfaction partially and simultaneously had a significant effect on employee performance within the Regional Disaster Management Agency of North Barito Regency.